Schaffer’s Method of Detorsion and Delivery of Triplets in a Non-Descript Goat - Saikumar, Savitha; Sengoda, Raja; Subramaniyan, Prakash; Subramanian, Alagar; Soundarapandian, Satheshkumar (The Indian Journal of Animal Reproduction, 2022)
A non-descript doe was presented with a history of full-term pregnancy and abdominal straining.  Clinical examination revealed a narrowing of the birth canal and twist of vaginal wall towards the clockwise direction, and the case was diagnosed as right side post cervical uterine torsion.  Schaffer’s method of detorsion was attempted and two dead female fetuses along with a live female fetus were relieved.  The doe was treated with antibiotics and other supportive therapy for two days. The animal showed an uneventful recovery.
Keywords: Non-descript doe; Post-cervical torsion; Schaffer’s method